MODEL PEMBELAJARAN PROBLEM BASED INTRODUCTION (PBI) DALAM DESAIN PRINTED CIRCUIT BOARD (PCB) BAGI MAHASISWA PRODI T. ELEKTRONIKA (D3) DAN P.T. ELEKTRONIKA (S1) FT UNY - Muhammad Munir (Faculty of Engineering, Universitas Negeri Yogyakarta, 2012)
ABSTRACKResearch purpose is know student trouble in developing ability desain PCB and determine steps that shouldbe done to increase ability desain PCB.Research design use survey method and by descriptive quantitative and qualitative. Population are ElectronicsTechnical Education and Electronics Technical students that take subject Technical Drawing teaching year 2010 /2011 and 2011 / 2012. Total respondents 34 persons from population which amounted 80 persons. Instrument usedis closed and open quesioner.Research conclusion: the most difficult in draw component symbol is transformator fingered by 38,24%respondents. The most difficult in draw code position component at PCB is arrange component a type of fingeredby 38,24% respondents. The most difficult in design band PCB is determine band junction fingered by 41,67%respondents. Steps that should be done to increase very ability design PCB for student that is: should be careful,patient, dilligence, make skets, read guide, use elektronics symbol pattren, learn from example, discussion withfriend, consider component used and measure, and early mendesain in paper millimeters block.Keyword : PBI, PBC design